Safety for the user of the feed additive consisting of ferric tyrosine chelate (TYFER™) for chickens, turkeys and minor poultry species for fattening or reared for laying/breeding (Akeso Biomedical, Inc) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2024)
Abstract Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel) was asked to deliver a scientific opinion on the safety for the users of the feed additive consisting of ferric tyrosine chelate (TYFER™) when used as a zootechnical additive for chickens, turkeys and minor poultry species for fattening or reared for laying/breeding. The European Commission request follows a previous opinion of the FEEDAP Panel. In that opinion, the Panel identified several risks for the users of the additive; it was listed that it posed a risk to users by inhalation, should be considered as an irritant to skin, eyes and mucous membranes, and also that, due to its nickel content, should be considered as a dermal and respiratory sensitiser. In the current application, the applicant proposed a maximum content of nickel (50 mg/kg). No changes in the manufacturing process have been reported by the applicant. In the absence of new data, the FEEDAP Panel reiterates its previous conclusion that the additive should be as an irritant to skin, eyes and mucous membranes and as a dermal and respiratory sensitiser.